(untitled) (Scientific journal of the Fergana State University, 2025)
This article examines the role of the category of negation in speech, particularly through excerpts from Abdulla Qodiriy’s historical-social novel “O‘tkan Kunlar” (Days Gone By), which portrays the socio-political events of 19th-century Central Asian states, and from “Kecha va Kunduz” (Night and Day), a novel reflecting the cultural, political, and socio-political events during the decline and dissolution of the Kokand Khanate under Russian rule in the early 20th century. The article explores how negation reflects the internal state of the characters, their thoughts, and emotions, focusing on the way each character addresses themselves in their inner speech. This internal dialogue highlights a key function of language—expressing thought—and reveals that inner speech should be studied not only within linguistics but also as a category of psychology. Additionally, the article discusses the main forms in which negation can be presented within linguistics.